The group law on a tropical elliptic curve - Vigeland, Magnus Dehli (MATHEMATICA SCANDINAVICA, 2009)
In analogy with the classical group law on a plane cubic curve, we define a group law on a smooth plane tropical cubic curve. We show that the resulting group is isomorphic to S^1.